PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KEKERASAN SEKSUAL SESAMA JENIS DI KABUPATEN BULELENG (Studi Kasus Putusan Nomor 1/Pid.Sus/2018/PN.Sgr) - Kadek Dwi Siva Juliani; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to (1) examine and analyze law enforcement against perpetrators of same-sex sexual violence in Buleleng Regency (2) examine and analyze the considerations of judges in deciding case Number 1/Pid.Sus/2018/PN.Sgr. Empirical legal research is used, with descriptive research characteristics. Primary and secondary data, consisting of primary, secondary, and tertiary legal materials, are the data sources used. For data collection, various techniques were used, including document studies, observation, and interviews. The sampling technique used is non-probability sampling, and the subject is determined by purposive sampling technique. Furthermore, the information collected is processed and examined qualitatively. The results of the study show that (1) law enforcement against perpetrators of same-sex sexual violence starts with reporting, investigation, arrest and detention, prosecution, trial, and execution of decisions (2) judges' considerations in making decisions against perpetrators of same-sex sexual violence in the case of case decision number 1/Pid.Sus/2018/PN.Sgr is Article 76 E Jo Article 82 paragraph (1) RI Law No. 35 of 2014 concerning Amendments to RI Law No. 23 of 2002 concerning Child Protection because the victim is a child which is regulated where based on the interpretation of the law, the principle of lex specialis derogat legi generali says that special law (lex specialis) overrides general law (lex generalis).